Influence of the Hydraulic Boundary Condition between the Embankment and Saturated Half-Space on the Train-Induced Ground Vibration. (11th February 2019) - Yuan, Zong-hao; Cao, Zhi-gang; Tang, Hao; Sun, Si
Abstract : A three-dimensional analytical model was proposed to investigate the influence of the hydraulic boundary of the ground surface on the train-induced ground vibrations. The ground was simulated as a fully saturated poroelastic half-space and the embankment as a rectangular elastic soil layer with finite width. The rails and the sleepers were modeled as Euler beams and a Kirchhoff plate, respectively. Two hydraulic boundaries of the interface between the embankment and the ground surface were simplified as two limiting cases, namely, the permeable and impermeable cases. The linearized dynamic equations of motion for the fully saturated poroelastic soil and the elastic embankment were solved by Fourier transform and Fourier series. The vertical velocity and pore pressure were firstly calculated in the frequency-wavenumber domain and then transformed into the time-space domain by inverse Fourier transform. The influence of the hydraulic boundary at the ground surface on the train-induced ground vibration was specially investigated. It was found that the hydraulic boundary condition has a significant influence on ground-borne vibrations for the high-speed moving train with high load excitation frequencies.